Binding and separation of CO2, SO2 and C2H2 in homo- and hetero-metallic metal–organic framework materials. Issue 11 (24th February 2021) - Briggs, Lydia; Newby, Ruth; Han, Xue; Morris, Christopher G.; Savage, Mathew; Krap, Cristina Perez; Easun, Timothy L.; Frogley, Mark D.; Cinque, Gianfelice; Murray, Claire A.; Tang, Chiu C.; Sun, Junliang; et al.
Abstract : MFM-300(Cr) and the mixed-metal MFM-300(Al0.67 Cr0.33 ) have been synthesised and characterised; their adsorption isotherms and host–guest interactions with CO2, SO2 and C2 H2 are investigated systematically. Abstract : We report the adsorption of C2 H2, CO2 and SO2 in a new, ultra-stable Cr(iii )-based MOF, MFM-300(Cr), {[Cr2 (OH)2 (L)], H4 L = biphenyl-3, 3′, 5, 5′-tetracarboxylic acid}. MFM-300(Cr) shows uptakes of 7.37, 7.73 and 8.59 mmol g −1 for CO2, C2 H2 and SO2, respectively, at 273 K, 1.0 bar, and shows a higher selectivity for SO2 /CO2 compared with the Al(iii ) analogue MFM-300(Al) (selectivity of 79 vs. 45). In order to monitor the effects of changing metal centre on gas uptake and to integrate the properties of the homometallic analogues, the mixed metal MFM-300(Al0.67 Cr0.33 ), [Al1.34 Cr0.66 (OH)2 (L)] has been synthesised. In situ synchrotron micro-FTIR spectroscopy has identified distinct CO2 binding environments on Al–O(H)–Al, Cr–O(H)–Cr and Al–O(H)–Cr bridges in MFM-300(Al0.67 Cr0.33 ), and we have determined the binding domains for these gases by in situ synchrotron X-ray diffraction in both MFM-300(Cr) and MFM-300(Al0.67 Cr0.33 ). The capability of these materials for gas separation has been confirmed by dynamic breakthrough experiments. The incorporation of Al(iii ) and Cr(iii ) within the same framework allows tuning of the host–guest and guest–guest interactions within these functional porous materials.